Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve using substitution. y = -2x - 10 y = 2x + 2 ( _ , _ )

Sagot :

Answer:

(-3, -4)

Explanation:

The system of equations is:

y = -2x - 10

y = 2x + 2

So, we can replace y by (-2x - 10) on the second equation as follows:

y = 2x + 2

-2x - 10 = 2x + 2

Then, we can solve for x:

-2x - 10 = 2x + 2

-2x - 10 + 2x = 2x + 2 + 2x

-10 = 4x + 2

-10 - 2 = 4x + 2 - 2

-12 = 4x

-12/4 = 4x/4

-3 = x

Finally, we can replace x by -3 on the first equation and get:

y = -2x - 10

y = -2(-3) - 10

y = 6 - 10

y = -4

So, the solution is the ordered pair (x, y) = (-3, -4)